KESALAHAN DI BIDANG KOHESI DAN KOHERENSI SERTA PENYEBABNYA PADA KARANGAN BAHASA JAWA SISWA SMP KELAS VIII DI KOTA PEMALANG (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The problem in this study are (1) the nature and type of errors in the essay cohesion and coherence of Java language, (2) for the purpose of cohesion and coherence errors decrypt forms, types and causes of errors cohesion and coherence in Javanese essay eighth grade students in the Pemalang, and thus the structural-functional approach. The result is that there is coherence and cohesion errors,  in Javanese student essay includes grammatical and lexical errors cohesion and coherence error. Cohesion grammatical errors include errors conjunctions and substitutions. Errors include the use of lexical cohesion is repetition and the use of pronouns. Errors include the terms of argumentative coherence, the cause of action, cause and effect, the parable. Error between paragraph coherence that is the relationship that is not coherent meaning between paragraph. Factors that led to the error of interference Indonesian and  Krama Javanese